Muzic Indians of the 18th century: the indigenous band of Itapecerica (1767-1835) - Goncalves, Daniel Issa [UNESP]; Castagna, Paulo [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2024)
Itapecerica was founded at the end of the 17th century as an indigenous mission, which, from an early age, registered the existence of a musical ensemble. An official letter from the governor of the Captaincy in 1767 requested the presence of its musicians in the festivities of the Fazenda Sant'Anna, and the censuses of 1773 indicate the existence of an indigenous organist and music master. In 1802, there were eight musicians among the villagers. Therefore, we undertook a search in the censuses of Santo Amaro (1766-1847), where the village of Itapecerica is also registered, in order to find more records of musicians active there. Then, comparing the results with those of the parish records of Itapecerica, we were able to reconstruct the biography of eighteen of these indigenous musicians, recovering their stories as well as that of the musical ensemble of the village, opening new research fronts on the musical activity in the missions.
Keywords: Itapecerica; Jesuitic Missions; Indigenous Musicians; Colonial Music; History of Music in Brazil